CD4+ T cell lymphopenia predicts mortality from Pneumocystis pneumonia in kidney transplant patients. Issue 9 (30th April 2020) - Freiwald, Tilo; Büttner, Stefan; Cheru, Nardos T.; Avaniadi, Despina; Martin, Simon S.; Stephan, Christoph; Pliquett, Rainer U.; Asbe‐Vollkopf, Aida; Schüttfort, Gundolf; Jacobi, Volkmar; Herrmann, Eva; Geiger, Helmut; et al.
Abstract: Background: Pneumocystis jirovecii pneumonia (PcP) remains a life‐threatening opportunistic infection after solid organ transplantation, even in the era of Pneumocystis prophylaxis. The association between risk of developing PcP and low CD4 + T cell counts has been well established. However, it is unknown whether lymphopenia in the context of post‐renal transplant PcP increases the risk of mortality. Methods: We carried out a retrospective analysis of a cohort of kidney transplant patients with PcP (n = 49) to determine the risk factors for mortality associated with PcP. We correlated clinical and demographic data with the outcome of the disease. For CD4 + T cell counts, we used the Wilcoxon rank sum test for in‐hospital mortality and a Cox proportional‐hazards regression model for 60‐day mortality. Results: In univariate analyses, high CRP, high neutrophils, CD4 + T cell lymphopenia, mechanical ventilation, and high acute kidney injury network stage were associated with in‐hospital mortality following presentation with PcP. In a receiver‐operator characteristic (ROC) analysis, an optimum cutoff of ≤200 CD4 + T cells/µL predicted in‐hospital mortality, CD4 + T cell lymphopenia remained a risk factor in a Cox regression model. Conclusions: Low CD4 + T cell count in kidney transplant recipients is a biomarker for disease severity and a risk factor for in‐hospital mortality following presentation with PcP.